A Global Convergence of LS-CD Hybrid Conjugate Gradient Method. (22nd October 2013) - Yang, Xiangfei; Luo, Zhijun; Dai, Xiaoyu
Abstract : Conjugate gradient method is one of the most effective algorithms for solving unconstrained optimization problem. In this paper, a modified conjugate gradient method is presented and analyzed which is a hybridization of known LS and CD conjugate gradient algorithms. Under some mild conditions, the Wolfe-type line search can guarantee the global convergence of the LS-CD method. The numerical results show that the algorithm is efficient.